Escape Mutations, Ganciclovir Resistance, and Teratoma Formation in Human iPSCs Expressing an HSVtk Suicide Gene - Andriana G Kotini; Elisa de Stanchina; Maria Themeli; Michel Sadelain; Eirini P Papapetrou (Elsevier, 2016)
Human pluripotent stem cells (hPSCs) hold great promise for cell therapy. However, a major concern is the risk of tumor formation by residual undifferentiated cells contaminating the hPSC-derived cell product. Suicide genes could safeguard against such adverse events by enabling elimination of cells gone astray, but the efficacy of this approach has not yet been thoroughly tested. Here, we engineered a lentivirally encoded herpes simplex virus thymidine kinase (HSVtk) with expression restricted to undifferentiated hPSCs through regulation by the let7 family of miRNAs. We show that induced pluripotent stem cells (iPSCs) expressing a let7-regulated HSVtk transgene are selectively killed by ganciclovir (GCV), whereas differentiated cells are fully protected. However, in contrast to previous studies, we find that in vivo GCV administration results in longer latency but does not prevent teratoma formation by iPSCs expressing either a constitutive or a let7-regulated HSVtk, without evidence of silencing of the HSVtk. Clonal analyses of iPSCs expressing HSVtk revealed frequent emergence of GCV resistance which, at least in some cases, could be attributed to preexisting inactivating mutations in the HSVtk coding sequence, selected for upon GCV treatment. Our findings have important consequences for the future use of suicide genes in hPSC-based cell therapies.